Google Suite For Education Application Analysis In Distance Learning At MI Miftahul Akhlaqiyah - Nur Khikmah; KHIKMAH, Mushlihah 'Ainur Rohmah (Kirana Publisher (KNPub), 2022)
The importance of implementing Google Suite for Education in schools is to achieve educational effectiveness through the provision of more innovative and communicative educational services. This research uses qualitative approach with a case study method in nature descriptive. Data collection tehniques by way of interviews, observation and documentation. Data analysis by means of reduction, data presentation and conclusions. The results of the study show that disrance learning using the Google Suite for Education is considered effective, (1) its application uses the Google Classroom service to manage online learning activities, Google forms to hold quizzes abd exam questions, and Google Meet for video conferencing. (2) The impact: eliminating teachers' lack of understanding of technology, making it easier for teachers to complete administrative activities, storing more structured data, sharing data and information, making it easier for student parents to monitor student progress, making it easier for students to study at home.